Elevating Batik Boutique’s Digital Presence: A Pathway to Sustainable Growth in The Fashion Industry - Suib, Fatin Husna; Muhd Alwin Liew , Melisa Nurjustina Elwiana; Md Nurdin, Khadijah; Bouchikhi Bushra; Muhammad Fuad Hafiy Md Khairuddin; Muhammed Adnan .P (IIUM Journal of Case Studies in Management, 2025)
Batik Boutique, a social enterprise based in Malaysia, exemplifies a successful intersection between cultural heritage and contemporary digital marketing. This case study explores Batik Boutique’s current digital marketing strategies, evaluates challenges in its execution, and proposes actionable strategies to strengthen brand presence and customer engagement. With a digital shift catalyzed by the COVID-19 pandemic, Batik Boutique expanded from minimal online operations to a multi-channel digital presence utilizing websites, SEO, social media, and e-mail marketing. Yet, it faces challenges like fluctuating ad performance and engagement, along with a low conversion rate. Proposed improvements focus on refining target segmentation, leveraging AI, enhancing retention strategies, and strengthening content variety. These adjustments aim to optimize brand engagement, elevate Batik Boutique’s digital impact, and support sustainable growth.